Micro and nanostructured phases obtained by mechanical alloying - low temperature annealing in AB5-H2 systems - Obregon, Sergio Alejandro (2015)
In this work, the characteristics of a commercial sample of LaNi5 are compared to those of an experimental one obtained by mechanical alloying followed by low temperature annealing. The nominal composition of the experimental sample is Mm-4Ni-1Al where Mm =La0.25Ce0.52Nd0.17Pr0.06. The morphology, nano, micro and structure of each sample are analyzed. Morphology is analyzed by both SEM and TEM. Micro and structure were studied by XRD and nanostructure by TEM. To the detection limits, the commercial sample is a mono phase. The mono phase possesses good crystalline characteristics closely related to samples obtained at annealing in near equilibrium conditions (T > 800 °C, t > 48 h). The Mm-4Ni-1Al sample has an AB5 structure as a major phase. The minor phases were characterized by XRD and TEM. The analysis is completed with the study of the hydrogen sorption properties of each sample. Finally, both types of properties are correlated. The opportunities of improvement of the synthesis method are discussed in relation to the investment costs of each production technique.